An Investigation into the Factors Influencing the Purchase Intentions of Smart Wearable Technology by Students - Nkonko, E.K.; Chiliya, N; Chuchu, T; Ndoro, T (International Association of Online Engineering, 2019)
The purpose of this study was to examine the factors which influence the purchase intentions of Smart wearable technology by students in South Africa. The researchers, guided by literature developed a conceptual framework with five constructs, namely, product quality, design, price, consumer attitudes and purchase intentions. The study followed a quantitative research design. Data was collected from 416 registered students at a selected higher education institution in South Africa who were older than 18 years. Data analysis techniques comprised of structural equation modelling which focused on confirmatory factory analysis to confirm conceptual relations and causal relations between the factors. SPSS 23 and AMOS 23 software were used to perform the data analysis. The results revealed that product quality and product design had a significant positive effect on purchase intentions. Price and attitudes were found to be mediating the effect of product quality and product design on purchase intentions. The paper contributes to existing literature on the purchase intentions of Smart wearable technology. Furthermore, it provides technology organisations with adequate insight into the factors which influence the purchase of Smart wearable technology. © 2019 International Association of Online Engineering.
Keywords: Higher education; Mobile application; Students; Technology